Reflections on Appellate Leadership - Elias, Sian (Victoria University of Wellington Law Review, 2002)
Chief Justice Elias discusses appellate leadership by exploring Sir Ivor Richardson’s judicial process during his time as President of the Court of Appeal. Judges must demonstrate professionalism and impartiality. However, judges must strike an appropriate balance between efficiency in dispatch of court business and ensuring that justice is not prejudiced. In terms of the mechanics of judicial reasoning, Sir Ivor Richardson was a pioneer in his exploration of a statute’s scheme and purpose in statutory interpretation. Where the statute was unhelpful, Sir Ivor did not shy from using common law as well as contemporary social values. However, Sir Ivor was also careful in his decision as some topics were unsuitable for judicial resolution. Chief Justice Elias concludes that Sir Ivor’s relentless search for sound judgment has made him a fine example of appellate leadership.